Tingkat Pendapatan Petani Akibat Alih Fungsi Lahan Pertanian Padi Menjadi Lahan Pertanian Jagung - Said Purwanto; Surdin Surdin; Sitti Kasmiati (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Land conversion is changing land use to increase the useful value of a piece of land. Change of land function, commonly referred to as land conversion, is a change in the function of part or all of a land area from its original function as planned to another function that has a positive or negative impact on the environment and the potential of the land itself. This research aims to determine the income level of rice farmers before the land is converted and the income of corn farmers after the land is converted. This type of research is descriptive qualitative research. Data collection techniques use observation and interviews. The research subjects in this study were all rice farmers who converted their land to corn farming in Kapu Jaya Village, totaling 26 people. The data analysis technique uses qualitative descriptive as a percentage table. The research results show that the average rice harvest income in one year for 2 tonnes produces Rp. 10,000,000, 4 tons makes Rp. 20,000,000, and 6 tons makes Rp. 30,000,000. Meanwhile, farmers' income after converting their land to corn farming for 9 tons on average produces Rp. 49,500,000, 18 tons produces Rp. 99,000,000. and 27 tons produces Rp. 148,500,000. Based on the results above, it shows that the income of Kapu Jaya village farmers increased after converting their land to corn farming.